Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10661-013-3166-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in soils along the coastal and estuarine areas of the northern Bohai and Yellow Seas, China

Abstract: Polycyclic aromatic hydrocarbons (PAHs) and their health risks in surface soils (n = 31) collected from coastal and estuarine areas of the northern Bohai and Yellow Seas (CEANBYS), China, were investigated. Total concentrations of PAHs ranged from 6.6 × 10(1) to 9.2 × 10(2) ng g(-1) dry weight, with an average of 3.1 × 10(2) ng g(-1) dw. The locations where greater concentrations of PAHs were observed were all near factories emitting black smoke or on the edge of the urban areas. These observations are consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…However, cancer risk (CR) for humans due to PAHs through soils in Gwalior, India were lower than Korba, India (adults, 6.7 × 10 −5 , children, 3.5 × 10 −5 , Kumar Wang et al 2013), Guangdong (8.45 × 10 −6 -2.94 × 10 −3 , Zhang et al 2011) in China, Niger Delta in Nigeria (adults, 6.19 × 10 −4 , children, 6.42 × 10 −4 , Olawoyin et al 2012). Comparatively, lower cancer risks to humans due to PAHs through soils have been reported from Bohai and Yellow Sea region (adults, 1.9 × 10 −6 , children, 1.6 × 10 −6 , Jiao et al 2013), Coking Plant Site (2.12 × 10 −4, Jia et al 2012), Guangzhou (3.03 × 10 −6 -2.92 × 10 −6 , Wang et al 2011) in China, Hong Kong (244 × 10 −6 , Man et al 2013) and from Delhi in India (adults, 1.2 × 10 −7 , children, 5.5 × 10 −7 , Kumar et al 2013a).…”
Section: Average Daily Intake Of Pahs and Lifetime Cancer Riskmentioning
confidence: 96%
See 1 more Smart Citation
“…However, cancer risk (CR) for humans due to PAHs through soils in Gwalior, India were lower than Korba, India (adults, 6.7 × 10 −5 , children, 3.5 × 10 −5 , Kumar Wang et al 2013), Guangdong (8.45 × 10 −6 -2.94 × 10 −3 , Zhang et al 2011) in China, Niger Delta in Nigeria (adults, 6.19 × 10 −4 , children, 6.42 × 10 −4 , Olawoyin et al 2012). Comparatively, lower cancer risks to humans due to PAHs through soils have been reported from Bohai and Yellow Sea region (adults, 1.9 × 10 −6 , children, 1.6 × 10 −6 , Jiao et al 2013), Coking Plant Site (2.12 × 10 −4, Jia et al 2012), Guangzhou (3.03 × 10 −6 -2.92 × 10 −6 , Wang et al 2011) in China, Hong Kong (244 × 10 −6 , Man et al 2013) and from Delhi in India (adults, 1.2 × 10 −7 , children, 5.5 × 10 −7 , Kumar et al 2013a).…”
Section: Average Daily Intake Of Pahs and Lifetime Cancer Riskmentioning
confidence: 96%
“…Li et al (2011) analyzed the relationship between health indicators of local residents and the PAHs levels in soils and found higher odds ratio and confidence interval for breast cancer, stomach cancer, dermatitis, gastroenteritis, and pneumonia. Cancer risk to human adults and children due to PAH exposure through soils has been reported worldwide by several workers (Zhang et al 2011;Diggs et al 2011;Wang et al 2011;Jia et al 2012;Obiri et al 2013;Williams et al 2013;Jiao et al 2013). Augusto et al (2012) found major cancer risk from soil (either ingestion or inhalation of re-suspended soil particles) in a petrochemical region in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…Records in China's Environmental Status Bulletin (1989 for chemical pollutants from industrial wastewater have focused on total nitrogen (TN), total phosphorus (TP), petroleum, oxygenconsuming organic matter, and heavy metals. There are also studies focused on emerging pollutants (ECs) (de Alda et al 2003;Jiao et al 2013;Meng et al 2015). Chemical pollutants from industrial sewage discharge can lead to the deterioration of water quality and degradation of habitats ( Figure 4).…”
Section: Impacts Of Industrial Effluents On Aquatic Ecosystemsmentioning
confidence: 99%
“…The recovery rates obtained were between 96.1% and 102.31% corresponding to Benzo(k)fluoranthène and Benzo(b)fluoranthène, respectively (Table 5). (6), Dibenzo(a,h)anthracene (7), Benzo(g,h,i)perylene (8) and Indeno (1,2,3,c,d)pyrene (9) 3. Indeed, the linearity test highlights the normality of the distribution across the range of the calibration range (0 to 1 mg/L).…”
Section: Validation Parameters For Pah Quantificationmentioning
confidence: 99%
“…From these origins arise environmental and professional exposure [7]. Food can be contaminated through the environment by PAHs from air, soil, water, automobile exhaust, and during industrial or domestic cooking or cooking [8,9]. Thus, PAHs have been detected in certain foods such as vegetable oils, seafood, meat, tea, coffee, rice, tomato, potato, fruit and infant foods [10,11,6].…”
Section: Introductionmentioning
confidence: 99%